High Pressure Laminates with Antimicrobial Properties - Magina, Sandra (2017)
High-pressure laminates (HPLs) are durable, resistant to environmental effects and good cost-benefit decorative surface composite materials with special properties tailored to meet market demand. In the present work, polyhexamethylene biguanide (PHMB) was incorporated for the first time into melamine-formaldehyde resin (MF) matrix on the outer layer of HPLs to provide them antimicrobial properties. Chemical binding of PHMB to resin matrix was detected on the surface of produced HPLs by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). Antimicrobial evaluation tests were carried out on the ensuing HPLs doped with PHMB against gram-positive Listeria innocua and gram-negative Escherichia coli bacteria. The results revealed that laminates prepared with 1.0 wt % PHMB in MF resin were bacteriostatic (i.e., inhibited the growth of microorganisms), whereas those prepared with 2.4 wt % PHMB in MF resin exhibited bactericidal activity (i.e., inactivated the inoculated microorganisms). The results herein reported disclose a promising strategy for the production of HPLs with antimicrobial activity without affecting basic intrinsic quality parameters of composite material.